Ost-westliche Erfahrungen der Modernität. Der chinesisch-deutsche Ideenaustausch und die Bewegung des 4. Mai 1919 - Mao, Mingchao (Chinese-Western Discourse, 2021)
The union of culture and politics that is so characteristic of modern Chinese history gained its first concise expression in the May Fourth Movement of 1919. The essays in this edited volume examine the exchange of ideas between China and Germany from various perspectives, illuminating how the clash between Chinese tradition and Western modernity accompanied and often inspired the movement.